Rural ecotourism: A qualitative analysis of exceptional sites from Southern Bengal, India - Satabdee Banerjee (Borneo Novelty Publishing, 2025)
Purpose - This study examines the economic, social, and ecological contributions of rural eco-tourism units in South 24-Pargana, West Bengal, India. These units focus on nursery gardens and organic farms instead of typical natural attractions, aiming to understand how such businesses can integrate tourism and achieve sustainability.Methodology/Design/Approach - A qualitative approach was used with three case studies of rural eco-tourism units. Data was collected through interviews with founders using semi-structured questionnaires and analyzed inductively.Findings - The study shows that eco-tourism can be both profitable and sustainable. Adding a tourism element to less successful businesses like nursery gardens and organic farms has made them economically viable. Visitors are willing to pay premium prices due to the ambiance, experience, and effective marketing.Originality - This study offers a unique perspective on rural eco-tourism in a region without traditional attractions, highlighting how tourism can enhance the viability of existing businesses. It emphasizes the role of social media, word-of-mouth, and government support in promoting such eco-tourism units.